Determinación de Babesia canis en perros con antecedentes de ectoparásitos atendidos en la clínica Dr. Darío Pet del cantón Ventanas Provincia de Los Ríos - Vera Chiriguayo, Erick Jhostin (2024)
Canine Babesiosis is an infection caused by a protozoan of the genus Babesia, which parasitizes the red blood cells of canines, multiplying and causing a febrile and hemolytic condition. It is transmitted by the tick of the genus Demacentor reticulatus and Rhipicephalus sanguineus, producing an infection in the canine. Acute, subacute and chronic, babesiosis is a zoonotic disease with worldwide distribution that can not only affect domestic mammals but also us humans, being a disease of public health interest. In the present experimental investigation, the purpose of this work is to determine Babesia canis in dogs with a history of ectoparasitosis that will be carried out at the Dr. Darío Pet veterinary clinic in the Ventanas Canton of the Province of Los Ríos, where sampling will be carried out on 50 canines of different breeds. , sex and ages, 1ml of peripheral blood will be extracted from the cephalic vein and then placed in a lilac-top vacuum tube with anticoagulant, a blood smear will be performed using the Giemsa staining method and a rapid test will be performed at 20%. After developing this research, the following results were obtained: By means of blood smears of the 40 samples, 23% were positive and 77% of the cases were negative, and by means of a rapid test the results found were 20% positive and 80% of the cases negative of the sampled animals. according to age from 6-1 months to 1 year 11% positive from 5-7 years 33% positive from 2-4 years 56% Through blood smear and rapid test the results obtained 5-6 Years 50% positive and from 3-4 years old, 50% were positive, based on the breed in the mixed breeds, a higher percentage of 34% positive was obtained through smears and by rapid test tests, 50% positive for the poodle breed was obtained. and the other 50% positive of the Pekingese breed, based on sex by the smear technique, 89% positive was obtained in males and 11% in females, thus finding a higher incidence according to sex, and through rapid testing 2 cases Positive results were found in females with 100% of the animals sampled.